A New History of British Documentary - Chapman, J. author. aut Link
XIV, 338 p.
Keywords: A New History of British Documentary is the first comprehensive overview of documentary production in Britain from early film to the present day. It covers both the film and television industries and demonstrates how documentary practice has adapted to changing institutional and ideological contexts.